1971
DOI: 10.2307/2004342
|View full text |Cite
|
Sign up to set email alerts
|

Roundoff Error Analysis of the Fast Fourier Transform

Abstract: Abstract. This paper presents an analysis of roundoff errors occurring in the floatingpoint computation of the fast Fourier transform. Upper bounds are derived for the ratios of the root-mean-square (RMS) and maximum roundoff errors in the output data to the RMS value of the output data for both single and multidimensional transformations. These bounds are compared experimentally with actual roundoff errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…While roundoff has traditionally been analyzed via a probabilistic model [42], it is not at all random (the magnitude of numerical error at the output of a finite-precision computation is a deterministic function of the inputs [43]). TPAD for FFT circuits allows the designer to specify an acceptable level T for numerical errors (which can be chosen based on the specifics of the arithmetic implementation).…”
Section: B Fast Fourier Transform Enginementioning
confidence: 99%
See 1 more Smart Citation
“…While roundoff has traditionally been analyzed via a probabilistic model [42], it is not at all random (the magnitude of numerical error at the output of a finite-precision computation is a deterministic function of the inputs [43]). TPAD for FFT circuits allows the designer to specify an acceptable level T for numerical errors (which can be chosen based on the specifics of the arithmetic implementation).…”
Section: B Fast Fourier Transform Enginementioning
confidence: 99%
“…However, since the FFT engine (like many arithmetic circuits in general [44]) is implemented with floating-point arithmetic, roundoff errors could corrupt the output, leading to many false positive Trojan detection outcomes. Hence, CED techniques that use comparisons of floating-point numbers to detect Trojans must have a way of distinguishing between errors due to finite-precision effects and errors due to attacks.While roundoff has traditionally been analyzed via a probabilistic model [42], it is not at all random (the magnitude of numerical error at the output of a finite-precision computation is a deterministic function of the inputs [43]). TPAD for FFT circuits allows the designer to specify an acceptable level T for numerical errors (which can be chosen based on the specifics of the arithmetic implementation).…”
mentioning
confidence: 99%
“…For example, the efficient access to the memory was an important issue in 1970s [56] just as it is today [21,23]. Another problem to be considered is the numerical precision [57].…”
Section: Fast Convolutionmentioning
confidence: 99%
“…with mean pa and variance <T2, we derive the following bounds on the expected value of the accompanying linear form for addition: (9) .…”
Section: Stochastic Roundoff Error Analysis 573mentioning
confidence: 99%
“…Owing to the dimensions of the vectors involved and to the need for repeated computations, the direct evaluation of the convolution product is usually prohibitively expensive [8]. While some studies of the rounding error for the fast Fourier transform can be found in the literature (see [2,6,7,9,12,14]), the issue of the numerical stability of circular convolution is only briefly addressed in [6].…”
Section: Introductionmentioning
confidence: 99%